Optimal Asset Allocation of Defined Contribution Pension Funds in Ghana - Baidoo Jnr, M. (University of Ghana, 2018)
The study investigated asset allocation of defined contribution (DC) plan in Ghana using the Tier 2 Master Trust Occupational Pension Scheme (MTOPS) as a case study. The focus of the study was to compare optimal asset allocation solutions under quantitative restrictions and prudent person’s principle and further assess the risk exposure of portfolio returns using CVaR. The financial market invested by MTOPS predominantly consisted of six financial assets: government securities and bonds, corporate bonds, the money market (T-Bills and Cash deposits), listed equities, other collective investments and open and close end funds. The investment returns from MTOPS followed a geometric Brownian motion and simulated for 10,000 scenarios over 50-year time horizon. Most MTOPSs violated some quantitative restriction guidelines such as Petra whose average allocation to the money market was 54.64% which exceeds 35% of the NPRA investment guidelines. However, the average investment returns of the six financial assets were within the limits. Beyond the investment restrictions, MTOPS allocated higher Master Trust Funds (MTF) in low-risk assets: government securities and bonds, T-bills and cash deposits. On the average, low-risk assets seem to be more rewarding and stable compared to high-risk assets in the short-term. High-risk assets however outperform low-risk assets in the long-term. Only MTOPS with large market share allocated considerably in high-risk assets: corporate bonds and listed equities. Financial assets were weak and negatively correlated which is indicative of a more diversified portfolios of MTOPS. The average MTOPS allocated 43.01% of MTF in government bonds and securities, 35.61% of MTF in the money market specifically in T-Bills and cash deposits, 18.30% in corporate bonds, 5.79% in listed equities, 3.02% in other collective investments, and 4.67% in open/close end funds. At optimal levels, MTOPSs are expected to invest 55.11% of MTF in government securities, 0.08% in corporate bonds, 34.99% in the money market, 0.81% in listed equities, 4.75% in other collective investments, and 4.98% in open/close end funds under quantitative restrictions. Applying the prudent person’s principle, optimal solution was obtained by investing 70% in government securities and bonds, 10% in corporate bonds, 10% in the money market, 7% in listed equities, 1.8% in open/close end funds and 1.2% in other collective investments. This indicated an investment return of 20.93% with 12.43% average portfolio risk as compared to 20.56% investment return with 6.79% portfolio risk in the restricted optimization. Given the investment returns over time, CVaR for the total portfolio was 12.81% at 95% confidence level in the worst-case scenario. The fund value based on current average allocations outperforms the optimal allocations in the long-term due to higher allocations of high-risk assets that accumulate higher returns in the accumulation phase. Keywords and Phrases: Defined Contribution; Master Trust Occupational Pension Scheme; Optimal Asset Allocation; Prudent Person’s; Principle Quantitative Restrictions
MPhil.
Keywords: Asset Allocation; Pension Funds; Ghana